Membangun Generasi Jujur: Peran Siswa dalam Gerakan Anti-Korupsi - Santi Rimadias; Vidiyanna Rizal Putri; Angga Fadillah; Izma Amalia Khairunnisa; Istifadah Azzahra; Firyal Nadia Zadien Rifa; Nova Astria; Holdeny Rifath (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2026)
This Community Service Program (PKM) aimed to enhance students’ understanding of anti-corruption education and strengthen the internalization of integrity values from an early age. The activity was conducted at SMAN 43 Jakarta and involved 36 students from class XA. The program employed interactive and participatory learning methods, including material presentations, educational games, group discussions, educational video screenings, question-and-answer sessions, and evaluation quizzes designed to assess students’ comprehension. The materials delivered covered the basic concepts of corruption, various forms and types of corruption, bribery practices, embezzlement cases, and examples of unethical behavior that may occur in students’ daily environments. The results indicated a significant improvement in students’ knowledge, awareness, and critical understanding of simple forms of corruption that are often overlooked or considered trivial. Furthermore, the participatory learning approach proved effective in increasing student engagement, encouraging active involvement throughout the activities, and fostering positive character development. Students demonstrated greater awareness of the importance of honesty, responsibility, discipline, and ethical behavior, both in the school environment and in their everyday social interactions.